Effect of abatacept treatment on serum osteoclast-related biomarkers in patients with rheumatoid arthritis (RA): A multicenter RA ultrasound prospective cohort in Japan. Issue 28 (16th July 2021) - Kawashiri, Shin-Ya; Endo, Yushiro; Nishino, Ayako; Okamoto, Momoko; Tsuji, Sosuke; Takatani, Ayuko; Shimizu, Toshimasa; Sumiyoshi, Remi; Koga, Tomohiro; Iwamoto, Naoki; Ichinose, Kunihiro; Tamai, Mami; et al.
Abstract : Abstract: We evaluated the effect of abatacept treatment on osteoclast-related biomarkers and explored whether the biomarkers are associated with the therapeutic response in rheumatoid arthritis (RA) patients treated with abatacept. We enrolled 44 RA patients treated with abatacept from a multicenter prospective ultrasound cohort study of patients who received biologic or targeted synthetic disease-modifying antirheumatic drug therapy. We evaluated the disease activity score (DAS) 28-CRP (C-reactive protein), musculoskeletal ultrasound scores including the total grayscale score (GS)/power Doppler (PD) score and the serum concentrations of isoform 5b of tartrate-resistant acid phosphate (TRACP-5b) and soluble receptor activator of nuclear factor-κB ligand (sRANKL) at baseline and at 3 and 6 months of treatment. "PD responder" was defined as a patient whose Δtotal PD score over 6 months was greater than the median change of that. Abatacept significantly improved DAS28-CRP as well as the total GS/PD score over 6 months. Serum TRACP-5b was significantly elevated and serum sRANKL was significantly decreased at 6 months ( P  < .0001 and P  < .01, respectively). At 6 months, serum sRANKL was significantly decreased in the patients who achieved DAS28-CRP remission and the PD responders but not in those who did not. However, serum TRACP-5b rose regardless of the therapeutic response. Among RA patients treated with abatacept, serum sRANKL decreased in the patients with a good therapeutic response, but serum TRACP-5b elevated paradoxically regardless of the therapeutic response. Abstract : Supplemental Digital Content is available in the text